VISUAL COMPOSITION IN BUILDING DRAMATIZATION OF SONG LYRICS IN THE MUSIC VIDEO “MELAWAN RESTU”: KOMPOSISI VISUAL DALAM MEMBANGUN DRAMATISASI LIRIK LAGU PADA VIDEO MUSIK “MELAWAN RESTU” - Sanjaya, William (VCD: Journal of Visual Communication Design, 2023)
Cinematography is about combining and capturing images to form a series of images that tell a story. In practice, cinematography has several compositions, such as the rule of thirds, visual composition, and camera angles. "Melawan Restu" is a music video that applies visual composition to highlight the theme of romance. Unlike other music videos, many visual compositions emphasize the meaning of each song’s lyrics. This study aims to show the visual composition that builds dramatization of the song lyrics in the music video "Melawan Restu". The method used is qualitative by using a purposive sampling technique. This study uses Gustavo Mercado's theory which discusses visual composition in cinematography. The results of this study indicate that visual composition not only provides aesthetics but also the meaning of each shot so that it can be understood by the audience. In the music video for "Melawan Restu", there is an application of the visual composition showing serenity which connotes the lyrics of the song. While several other visual compositions show sadness, powerless, and turmoil in the bad situations experienced by the female characters in the story.